Réponses

  • Omnes
  • Modérateur confirmé
2014-03-27T18:30:27+01:00
Salut,

(2x+3)(4-x)  ≥ 0
2x + 3 ≥ 0
2x ≥ -3
x ≥ -3/2

4 -x ≥ 0
-x ≥ -4
x ≤ 4

S = [-3/2; 4]


B(x) =  \frac{2x}{5x + 3} -1\\
B(x) =  \frac{2x}{5x + 3} -  \frac{5x + 3}{5x + 3} \\
B(x) =  \frac{2x - (5x + 3)}{5x + 3} \\
B(x) =  \frac{-3x - 3}{5x + 3} \\

B(x)  \geq 0\\
 \frac{-3 - 3x}{5x + 3 }  \geq 0\\
5x + 3  \neq 0\\
5x  \neq -3\\
x  \neq  -3/5\\
-3 - 3x  \geq  0\\
-3x  \geq 3\\
x  \leq -1\\

S = ]-\infty; -1]\\
B(x)   \leq  0\\
x  \geq -1\\
S = [-1; + \infty[


Bonne soirée!
Merci beaucoup beaucoup, (a partir D'ou commence la question 2b )